Photoresponsive Inorganic Nanomaterials in Oncology - Francesco Barbero PhD; Shagufta Gul MS; Guido Perrone PhD; Ivana Fenoglio PhD (Technology in Cancer Research & Treatment, 2023)
The diagnosis and treatment of cancer are continuously evolving in search of more efficient, safe, and personalized approaches. Therapies based on nanoparticles or physical stimuli-responsive substances have shown great potential to overcome the inherent shortcomings of conventional cancer therapies. In fact, nanoparticles may increase the half-life of chemotherapeutic agents or promote the targeting in cancer tissues while physical stimuli-responsive substances are more effective and safer with respect to traditional chemotherapeutic agents because of the possibility to be switched on only when needed. These 2 approaches can be combined by exploiting the ability of some inorganic nanomaterials to be activated by light, ultrasounds, magnetic fields, or ionizing radiations. Albeit the development of stimuli-responsive materials is still at the early stages, research in this field is rapidly growing since they have important advantages with respect to organic nanoparticles or molecular substances, like higher stability, and higher efficiency in converting the stimulus in heat or, in some cases, reactive oxygen species. On the other hand, the translation process is slowed down by issues related to safety and quality of the formulations. This literature review summarizes the current advancements in this research field, analysing the most promising materials and applications.